Saphenovenous Graft Aneurysm: A Rare Complication of CABG - James Thomas Connell (Case Reports in Cardiology)
Saphenovenous graft aneurysm is a rare complication of coronary artery bypass grafts that is likely underdiagnosed. It is typically asymptomatic, slow growing, and often diagnosed incidentally on angiography or following catastrophic rupture. There is no consensus on best management but PCI and surgery appear to have more favourable mortality outcomes relative to conservative management. We present the case of a 48-year-old male with a cardiovascular risk profile hallmarked by diabetes mellitus, end stage renal failure, recalcitrant hyperlipidaemia, and IHD previously treated with CABG. 11 years following his CABG, he was retrieved from remote Australia to a tertiary cardiology centre with stabbing chest pain. Serial cardiac enzymes were negative. Echocardiogram identified a mass compressing the right ventricular wall. Noncontrast coronary angiogram ultimately identified a large aneurysm at the proximal end of SVG to PDA. He was managed with aggressive risk factor modification prior to planned surgical intervention once medically optimized. His case supports the role of aggressive medical management combined with surgical intervention.